1997
DOI: 10.1210/en.138.1.237
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of Guinea Pig Cyclooxygenase-2 and 15-Hydroxyprostaglandin Dehydrogenase Complementary Deoxyribonucleic Acids: Steroid-Modulated Gene Expression Correlates to Prostaglandin F2  Secretion in Cultured Endometrial Cells

Abstract: Prostaglandin F 2␣ (PGF 2␣ ) secretion is lowest at midcycle and highest on day 15 at luteolysis in the cycling guinea pig uterus and is inversely related to serum progesterone levels. An increase in 17-␤ estradiol (E 2 ) occurs only towards the end of the cycle. To investigate the effect of steroids on the control of uterine PGF 2␣ metabolism at the level of gene expression we established a primary cell culture model of day 15 cycling guinea pig endometrial cells. We cloned guinea pig cDNAs for cyclooxygenase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…These domains include a putative transmembrane region, heme-coordinating histidines 295 and 374, the cyclooxygenase active-site tyrosine 371, the aspirin acetylation-site serine 516, and four putative N-linked glycosylation sites (DeWitt et al 1990;Shimokawa and Smith 1991;Lecomte et al 1994;Wennogle et al 1995). The presence of multiple repeats of the ShawKamen's sequence (5Ј-ATTTA-3Ј) in the 3Ј-untranslated region in the porcine COX-2 transcript is also a feature reported for COX-2 in several other species (Kujubu et al 1991;Hla and Neilson 1992;Feng et al 1993;Bracken et al 1997;Zhang et al 1996;Guan et al 1997;Boerboom and Sirois 1998;Song et al 1998;Liu et al 2001). This motif has previously been shown to be present in several immediate early genes and to confer instability to mRNAs (Caput et al 1986;Shaw and Kamen 1986).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…These domains include a putative transmembrane region, heme-coordinating histidines 295 and 374, the cyclooxygenase active-site tyrosine 371, the aspirin acetylation-site serine 516, and four putative N-linked glycosylation sites (DeWitt et al 1990;Shimokawa and Smith 1991;Lecomte et al 1994;Wennogle et al 1995). The presence of multiple repeats of the ShawKamen's sequence (5Ј-ATTTA-3Ј) in the 3Ј-untranslated region in the porcine COX-2 transcript is also a feature reported for COX-2 in several other species (Kujubu et al 1991;Hla and Neilson 1992;Feng et al 1993;Bracken et al 1997;Zhang et al 1996;Guan et al 1997;Boerboom and Sirois 1998;Song et al 1998;Liu et al 2001). This motif has previously been shown to be present in several immediate early genes and to confer instability to mRNAs (Caput et al 1986;Shaw and Kamen 1986).…”
Section: Discussionmentioning
confidence: 73%
“…Comparative analysis showed that the amino acid sequence of porcine COX-2 is very similar to that of other mammalian homologues, being 89%, 88%, 87%, 90%, 91%, 91%, 90%, 88%, 87% to human, rat, mouse, horse, cow, ovine, rabbit, guinea pig, and mink COX-2, respectively (Kujubu et al 1991;Hla and Neilson 1992;Feng et al 1993;Zhang et al 1996;Bracken et al 1997;Guan et al 1997;Boerboom and Sirois 1998;Song et al 1998;Liu et al 2001). The porcine enzyme includes all known structural and functional domains involved in COX-2 activity.…”
Section: Discussionmentioning
confidence: 99%
“…It is now evident that the stability of the mRNA plays one role in the regulation of COX-2 (Ristimaki et al 1996;Gou et al 1998;Cok and Morrison 2001;Dixon et al 2000Dixon et al , 2001Dixon et al , 2003. In addition, alternative COX-2 transcripts differing only in their 39-UTRs have been found in a number of cell and tissue types (Ristimaki et al 1996;Bracken et al 1997;Lukiw and Bazan 1997;Newton et al 1997Newton et al , 1998Dixon et al 2001;Schmidt et al 2003). Therefore, RNA stability and alternative 39-end processing are two important regulatory mechanisms that can contribute to the expression control of COX-2.…”
Section: Introductionmentioning
confidence: 99%
“…PGDH cDNA has been cloned from several species and organs, including human placenta, mouse lungs, rat intestine, and bovine and porcine uterus (Ensor et al 1990, Matsuo et al 1996, Bracken et al 1997, Zhang et al 1997, Parent et al 2006. Human PGDH encodes a protein of 266 amino acids with an apparent molecular weight of 29 kDa (Ensor et al 1990).…”
Section: Introductionmentioning
confidence: 99%